THE IMPLEMENTATION OF DIRECT READING STRATEGY IN TEACHING DESCRIPTIVE TEXT TO HELP READING COMPREHENSION TO THE SEVENTH GRADERS (RETAIN, 2014)
THE IMPLEMENTATION OF DIRECT READING STRATEGY IN TEACHING DESCRIPTIVE TEXT TO HELP READING COMPREHENSION TO THE SEVENTH GRADERS SKRIPSI Presented to Surabaya State University as a partial fulfillment of requirement for the Bachelor of art in English Language Education AGBELLA SHANDY ARSHINTA 092084028 STATE UNIVERSITY OF SURABAYA LANGUAGE AND ART FACULTY ENGLISH DEPARTMENT 2014 THE IMPLEMENTATION OF DIRECT READING STRATEGY IN TEACHING DESCRIPTIVE TEXT TO HELP READING COMPREHENSION TO THE SEVENTH GRADERS Agbella Shandy Arshinta English Education Department, Language and Arts Faculty, Surabaya State University. Email: agbellashandyarshinta@gmail.com Dr. Oikurema Purwati, M.Appl English Education Department, Language and Arts Faculty, Surabaya State University. Abstrak Bahasa Inggris untuk pendidikan biasanya digunakan sebagai pengenalan bahasa Inggris yang dapat diterapkan dalam empat keterampilan, seperti mendengarkan, membaca , berbicara dan menulis . Membaca adalah kemampuan untuk mengerti makna dari halaman cetak dan menginterpretasikan informasi yang diperoleh dengan tepat . Membaca merupakan keterampilan penting yang dapat menerima beberapa studi khusus sekaligus. Selain itu, membaca sangat berguna untuk mendapatkan lebih banyak kapasitas komponen bahasa ( kosakata , tata bahasa , dan pengucapan ) . Kegiatan direct reading ini dipilih untuk penelitian karena sangat berguna untuk mengembangkan pemahaman membaca siswa . Hal ini didukung oleh Betts ( 1946 ) yang mengatakan bahwa kegiatan direct reading dapat digunakan untuk memperluas dan memperkuat keterampilan membaca , karena kegiatan ini dapat memantau siswa - siswa dalam pemahaman tentang teks ketika mereka membaca. Peneliti memilih deskriptif kualitatif sebagai metode penelitian. Observasi , nilai tugas dan hasil wawancara digunakan untuk media mengumpulkan data . Dari data tersebut, peneliti membuat deskripsi dan analisis untuk menjawab pertanyaan dalam penelitian . Hasil dari lembar observasi menunjukkan bahwa guru menerapkan kegiatan direct reading dalam tiga pertemuan. Dengan menerapkan kegiatan tersebut , guru diharapkan dapat membuat situasi yang menarik dan efektif dalam belajar bahasa Inggris . Hasil siswa membaca dan tugas mereka menunjukkan bahwa sebagian besar siswa menunjukkan kemajuan dalam beberapa aspek membaca seperti konten , pengorganisasian , kosakata, penggunaan bahasa dan mekanik . Disimpulkan bahwa kegiatan direct reading ini sangat membantu untuk siswa pemula yang ingin belajar bahasa Inggris . Kata Kunci: Teks Deskripsi, Pemahaman membaca, Direct reading strategy Abstract English for education is usually used as an introduction to English. English can be applied in four skills, such listening, reading, speaking and writing. Reading is an ability to draw meaning from a printed page and to interpret the information appropriately. Reading is an essential skill which can receives several special focuses. Besides, reading is very useful to get more capacity of language components (e .g. vocabulary, grammar, and pronunciation). Direct reading activity is chosen to this research because it is very useful to develop the students’ reading comprehension. It is supported by Betts (1946) who said that direct reading activity can be used to expand and strengthen the students’ reading skill, because this activity can monitor the students’ understanding about the text while they are reading. The researcher chose descriptive qualitative as the research design.Observation sheet, tasks result and interview form were used to collect the data. From the data, the researcher made description and analysis to answer the research questions. The results from observation sheet shows that the teacher implemented direct reading activity on three meetings. By implementing those activity, the teacher can make an interesting and effective situation in learning English. The result of students reading tasks shows that most students made progress in some aspects of reading such as content, organization, vocabulary, language use and mechanic. Means that direct reading activity was very helpful to beginner who wants to learn English. Keywords: descriptive text, reading comprehension, direct reading activity. INTRODUCTION English is very important to communicate with other people around the world, because it has many relationships with various aspects of life such as education. English for education is usually used as an introduction to English. Then, people who learn English will know and understand about what English is look like in the first time. English gives some effects to the Indonesian people, exactly for education. English is considered as a foreign language and taught formally from elementary school to the university level. Because of this situation, some people believe and hope that by learning English as an introductory from primary school level, it will increase students’ ability for the next level and will give some advantages to make a good communication with other people by using English which can be applied in four skills, those are listening, reading, speaking and writing. Listening and reading are known as receptive skills, speaking and writing are known as productive skills. Reading is an ability to draw meaning from a printed page and to interpret the information appropriately.Reading is the most important skill which can be mastered to ensure success, not only in learning English, but also in learning any content where reading is required. By strengthening the reading skill, the learner will make a greater progress and development to other area of learning. In teaching reading, the teacher should be creative to teach students because the main objective of reading based on the Nuttal (1985), Baradja (1984), and Sadtono (1997) is to achieve comprehension. The result of teaching reading can affect the students’ attitude of perception. But in real situations, some expert say that reading ability of secondary school is still poor (Sadtono, 1988: Huda 1994).Some students still cannot read their textbooks well, it means that the students who cannot read, they cannot absorb the information on the text well. The mastery of reading is still a significant problem in today's school (Leo, 1997:176). It means that the mastery of reading skill becomes frequently essential problem faced by the students. Junior high school levels is the most decisive period for students to be able develop their potential better than before. The students are categorized into adolecents who is seen as problem students, but they also can be the most exciting students of all. Teaching reading to junior high school students, the teacher needs to be more active and creative to build their motivation to read and engage their knowledge about English. Harmer (2007:26) stated that a good teacher is someone who knows our names. For those statement, good teacher is a teacher who is able to understand their feeling and lead them to achieve their success in both academic and attitude. Therefore, in teaching reading the teacher need a strategy which able to attract the students’ interest and make them easily to comprehend the content of reading materials. There are many strategies which can the teacher implement in teaching learning process to the junior high school students, for example direct reading activity. “Direct reading activity is a strategy that provides students with instructional support before, during, and after reading. The teacher takes an active role as his or she prepares students to read the text by pre teaching important vocabulary, eliciting prior knowledge, teaching students how to use a specific reading skill, and providing a purpose for reading. (Betts. E.A: 1946)”. Based on those statement, direct reading activity can be implemented and guided students by asking questions about the text and making predictions about the whole text means. Before they are reading, the teacher asks some questions individually about the general text to monitor their comprehension. Then, the teacher asks the students to read the whole text. After reading, the teacher engages students in a small discussion focus on the purpose of reading. By implementing direct reading activity, the students will be more active and can be a thoughtful / critical reader, also enhance their comprehension. The writer chooses direct reading activity because it is very useful to develop the students’ reading comprehension. This activity can monitor the students’ understanding about the text while they are reading. Alamasa (2003) stated that the goal for using directed reading activity is to foster students’ independence when they are reading. It means that this strategy engages the students to be active where they have to use their own knowledge and their idea to give an argument. Based on Chung Shan’s observation (2000) in Taiwanese college, most of students in that college have a low reading comprehension scores. Fourty five subjects took part in the interview which analized by using qualitative research. The result indicated that there are certain concepts about EFL in reading skill. They showed a little awareness of independent reading. Many and Flyfe (1996) also examined the effectiveness of using direct reading activity to promote reading achievement and higher order thinking skills. The researchers applied an achievement reading test on 51 students. The result indicates significant gain in reading achievement, and the conclusion is students’ achievement can be improved by using this strategy. Dougherty Stahl (2004) explored the effects of three instructional strategies, the direct activity on the reading comprehension and science content acquisition of novice readers. The participants were 31 students. The results indicated that the direct reading activity yielded statistically significant effects on fluency, text comprehension, prediction justification, and prediction verification. Riley (2006) also investigated the effect of direct reading activity on low reading achievement in a first grade students. The study results indicated the possibility of correcting most of errors made by students while reading when they use direct reading activity. The study emphasized the importance of using direct reading activity to increase reading achievement and to promote critical thinking activity. Direct reading activity has been implemented in several junior high school in Ponorogo, who’s applied by Puspitasari (2011). She has implemented this strategy because she found the teaching learning process which was just translating the text to Bahasa Indonesia and then answering the question. This process absolutely makes some of the students bored. Only a few students who can paid attention, another just listen what the teacher said, but they did not understand about the content which they had read. Most of them got the low scores from minimal score-standard. They got difficulty to understanding and comprehending the text. When she implemented this strategy, the first step which she did was making the condition of the class become more comfortable. Giving some motivation to build their awareness in reading. She chose descriptive text, because of it have many info’s that can students get to understand the content. Before reading, teacher give some questions as the purpose to guide the students’ comprehension, such as making prediction in their own ideas, and finding the unfamiliar words.After that, teacher ask the students to read the text silently, to make sure that students have already understood or not. After reading, the teacher make a small discussion to shared and asked them about what have the students got before and after reading the text. When the student’s prediction wasn’t true, the teacher should guide them to get the correct one. The students will be an active reader by use this activity. And the result, by using this strategy, the students will be more active to present their own ideas, have more understanding about the whole text, and they got a better scores in EFL. Therefore, the researcher wanted to conduct a research which intends to describe this phenomenon, the implementation of direct reading activity to teach descriptive reading comprehension to the seventh grades students. By conducting this study, the researcher has purpose to find out the resultof the quality both of the teacher who are taught and students in a junior high school in Ponorogo. By knowing the fact or the result of the study, the researcher hoped it will give meaningful contribution for English teacher junior high school since it is important to be more creative to teach the students in order to increase their competency on mastering the teaching material especially motivation to read the English texts. It is also expected to give meaningful contribution for school. It is important to know about students’ ability when they study English in order to guarantee that their teachers are competent in mastering the teaching material in a various learning strategies. This phenomenon makes the researcher puts her interest to conduct research about it. The researcher also make questions as a follows: 1. How is the implementation of direct reading activity to the students’ reading comprehension about descriptive text? 2. How is the student’s ability in reading descriptive text when they implement direct reading activity? METHOD Based on the research question and the objective of the study, the researcher used descriptive qualitative. Descriptive research studies are designed to obtain the information concerning the status of phenomena (ary, et al. 1985:322). The aim of this study is to describe a natural situation without giving manipulation or special treatment to the subject of the research. another expert, named Sukmadinata (2006:18) stated that descriptive research is a research which aims to describe a situation or natural phenomenon and it is done without manipulation or giving special attention to the subject of the research because all of events or activities grow nature. The process of implementation direct reading activity and the result of teaching descriptive text by implementing direct reading activity to the seventh grade students are designed into a form of words.In this research, the researcher chose descriptive qualitative as the research design based on two reasons, which are the objective of this study is to describe the implementation of direct reading activity to teach descriptive reading comprehension. The subject of the study were the seventh grade students’ of Muhamadiyah 3 Junior High School Ponorogo. The reason why the researcher chooses the seventh grade students because descriptive text is one of the essential lesson in second semester for those junior high school students. She wants to know how to make the students easily to understand the material without make the students bored. The teacher said that the goal of teaching reading in this school is not yet totally achieved. This phenomenon arises because of some problems. The students’ reading comprehension is very low. They just read the text but they didn’t understand and catch the meaning of the text that they read. So, as a result the students often forgot about what they had read. Besides, the students often stopped reading because the text which given by teacher was too difficult and hard to be understood. Then, reading classroom activities made the students bored and the students did not interested in reading activity anymore.. This study is taken place in a classroom and school canteen of Muhammadiyah 3 Junior High School Ponorogo. The writer chooses Muhammadiyah 3 Junior High School Ponorogo, because the situation is not crowded, and more comfortable to conduct the research. The location of this school is strategic, and easily to get a public transportation. For the next, the writer will collecting the data through observation, because the writer wants to know the process of direct reading activity in the classroom. The writer become an observer or non-participator and she will use the observation sheets completely to know the result before and after the implementation of this strategy. Then, the writer make a list of questions to interview the teacher who will implements the technique. And last, the writer also make some documentations such as the result of study during teaching learning process. Hopkin (2008:157) states that interview is a way to know about the certain situation in a classroom from another point of view. That is why, the researcher interviewed the English Teacher to get more data relate to the implementation of the strategy and students ability. Besides, according to Arikunto (2006:56) observation is a convergence activity toward the object by using all the five sense. In this research, the purpose of using this instrument is to observe the teaching learning process, especially the teaching technique which used by the English teacher. The purpose of those observations is to answer the first research question. In this case, the researcher tried to observe the data about the class activities. The last instrument is collect the result of students’ exercises which given by the teacher. The writer only take the scores from the teacher. This documentation was needed to answer the second research question. From this documentation, the writer will discover about the students’ improvement after implementing direct reading activity to the class. After all of data accumulated, the researcher studied the data well, she described them by classifying into the finding based on the research question. In addition, all the data were collected thoroughly as happened in the reality. RESULT AND DISCUSSION This chapter presents the result and discussion of the study as the answers for the research questions: 1. How is the implementation of direct reading activity to the students’ reading comprehension about descriptive text? 2. How is the student’s ability in reading descriptive text when they implement direct reading activity? The Implementation of Direct Reading Activity to Teach Reading Comprehension to the Seventh Grade Students about Descriptive Texts The researcher conducted the observation at the seventh grade students of Muhammadiyah 3 Junior High School in three meetings at 11th, 13th, and 18th of June 2013. While conducting research, the writer made a list of the implementation of direct reading activity and the students’ response when they are reading by using direct reading activity. The result was based on the two research questions. As a result, the implementation direct reading activity in teaching reading descriptive text had some points that could be compared further. The points were dealing with the topic, the technique and the teaching learning process in Muhammadiyah 3 Junior High School. The topic here refers to the material given in the class. The topic was about reading descriptive text. It was suitable with the curriculum standard, because in that school descriptive text begin to be taught in seventh grade. Furthermore, the topic was also understandable and could lead students to be an enthusiastic reader. Even though they faced some difficulties in those activity, they were still enthusiastic to express their own idea after reading because the topic was in line to the students’ level and concerned with their daily life. The technique here refers to the implementation of direct reading activity to teach reading descriptive text. Since the teacher and students could implement those activity in teaching learning process, it means that this technique was applicable. The students were participated actively in the class because the technique encouraged them to share their opinions in the group work or individually. Furthermore, the technique also motivated the students and helped them to solve their difficulties in getting ideas to understand and comprehend the text means. It is in line with Alamasa (2003) who states that direct reading activity is to foster students’ independence when they are reading, means that this activity can engages the students to be active use their own ideas based on their background knowledge to make an arguments or opinions about text. And the last was the teaching learning process which refers to the activities which happened during the implementation of direct reading activity. At the first meeting, the teacher explained about descriptive text. After the teacher explained, there were some questions from the students. Apparently, the students can get the material easily. Then the teacher gave an example of descriptive texts and asked the students some questions to monitor their comprehension. Some of students could answer them well but some students seemed are not seriously and not interested in it. After explaining that, the teacher leads the discussion to build a motivation to the students. There were students who ask the unfamiliar word on a text, and wanted to know the meaning. But the teacher asked them to find the meaning on a pocket dictionary as a reason that she was forgotten about it. After all of unfamiliar word have finished to translate, the teacher checked their comprehension in a short question related to the text. The students allowed to answer the question with their own word, but still in English. After give some simulations, the teacher gave the students a sample of descriptive text then ask them to read by themselves. The teacher also give a good way to read the text correctly, then some of the students imitate her style. Teacher makes a notes to measure their ability to read that is correctly or not. Some students tried to read it in a loud voice, but still have lack of good pronunciation. The teacher gave a sample how to read a text again but in slowly version to help students who are still have difficulties to pronounce the word. At the second and third meetings the students did the same things as the first one, but it was slightly different. In the second and the third letters they had not only read but also responded to questions in an exercise which given by teacher. Before answering, the teacher asked the students to make sure that they already understand of what they have read, so they can do the exercises appropriately. To build their comprehension, the teacher makes some inference all the time. Then the students develop the teacher’s clues in their own idea. Means that students who get difficulties to understand, the teacher should help them to find out the solution, which give a clues to make student easier to grasp the meaning. This step is supported by William Lutz who defines an inference as a statement about the unknown based on the known (1996). By connecting some fact based on the texts’ discussion, comprehension will be get easily. While the students do the exercise, the teacher walked around the class to see if there was any students who needed her help. Some students consulted their difficulties such as in finding the words translation, and the correct meaning, while the others just asked their answer keys. The exercise was not done, because the time has finished, so the teacher asked the students to finish it at home as their homework and would be discussed to the next meeting. Direct reading activity can enhance students’ vocabulary as students will get a lot of input of new words from their text. Teacher’s comments and suggestions can also be the meaningful input for the students in improving their understanding. In answering the questions, students also activating their own ideas based on their knowledge before, to make a good sentence to answer the questions. Finally, the students were used to read, especially on their own willingness, their spelling and fluency in reading the text because of this frequent activity. Their sense of understanding the sentence’s means were gradually improved by itself as students frequently read. Nevertheless, there were some weaknesses in the implementation of direct reading activity by the teacher. In larger classes, this strategy is not properly applied and teaching in this strategy does not suit or satisfy the needs of individual students in large classes. Because in reading comprehension the students need more teacher helping to understand the content, and when the students are too much, it is difficult to the teacher to make sure that the student was get the point clearly or not. There also have many abstract words which cannot be interpreted directly in English and much time and energy are wasted in making attempts for the purpose. The Analysis of Students’ Works The researcher could see some improvements in teaching and learning process through the implementation direct reading activity, such as: 1) The students had high motivation to learn. So, the students could be control well. 2) Most of students understood about the text’s means, and 3) Students’ vocabularies increased although it was not extremely. The researcher observed the students’ work when the teacher had been done to give a score toward them. Based on the procedure of using direct reading activity, the writer said to the teacher to choose several students as a sample of her observations. Based on the interview transcript, The teacher said that the direct reading activity is an essential strategy to build students’ motivation to reading text as much they can, because they will know more in vocabularies, contents, and it will stimulate them to build their own main idea when they asked to tell the story by the teacher. For beginner, the seventh grade students still need a guidance to learn more about English and direct reading activity can help them to solve the students’ problem in learning and practicing English. It was absolutely appropriate to make a critical reader even though from the beginner level because by using direct reading activity, the students have their own words to express and retell the stories as much simple they can. Direct reading activity is one of useful and very helpful to monitor the students’ comprehension and understanding to the teaching learning process. The teacher gave supporting points to convincing the writer’s statement that implementing the direct reading activity is not a difficult to practice. When the teacher wants to implement to the classroom, they only need more patient to guide the students’ ideas and help them to understand and get the points easily. Besides, the teacher said that they had a language laboratory to practice listening, languages library which offered so many English books and dictionaries to help them find the meaning or unfamiliar words and build their motivation to learn or just an introductory to learn English. She said that the headmaster always supports the students’ activity positively, never gave a negative responses which can make the students lost their confidence then did not want to build their ability. All of the teacher and the headmaster always have the same mission to support students’ progress to build their creativity in their own way. The researcher observed the students’ work when the teacher had been done to give a score toward them. Based on the procedure of using direct reading activity, the researcher said to the teacher to choose several students as a sample of her observations.Five students as sample of practicing good reading are chosen by the teacher.Then some of them are allowed to show their reading ability by asking unfamiliar words to the teacher, and the teacher helped them to explain by writing the words to the board then translate into the new meaning related to the text. Those activity were able to measure how far the students’ reading comprehension after they read and knew the whole meaning of text. When the students have already understood, the teacher give simulation by giving some cause - effect questions orally to build students’ character of thinking, whether they could be a critical reader or not. The questions are: a. What do you already know about Mr. Hadi’s house? b. Do you think that Mr Hadi’s house is very comfortable? Finally, the teacher give a point to appreciate what her students do, means that the students are active to explore their own ability on the first meeting. In the second meeting, the writer observed the teaching learning process again. Most of students got a good score, butanother still needed to practice more at home. As the result, the teacher could give a good performance of implementing direct reading activity. And the third meeting as the last meeting of the observation, the teacher gave a new exercise to students about short letter from Lily. Teacher read the letter, and the students paid attention of her. After reading the letter, the teacher asked them to read by themselves. The next activity, teacher walked around into the class, to make sure that all of students read it seriously. For once, the teacher asked the student a simple question orally to tested that the student had already read or not, such “what did the two girls do based on the text that have been discussed?” The student could answer correctly even in wrong words, and the teacher helped them to correct it into the good one. And, most of them could explain their answer briefly means that they have understood about the text. The teacher was successful build students’ motivation to read and make them an active reader. Based on this situation, the researcher have a conclusion that direct reading activity was success to be implemented to the seventh grade students in Muhamadiyah 3 junior high school. The Students’ Ability during the Implementation of Direct Reading Activity to Teach Reading Descriptive Texts The researcher have known the students’ responses toward the implementation of direct reading activity in teaching learning process to teach reading when she observed the classroom. All of the students were given a positive response during the implementation. Most of students got a good score for reading and answering questions, they also have understood about the text means, so the students’ comprehension are built by the teacher’s motivation, and the implementation of direct reading activity. Overall, the implementation of direct reading activity had positive responses from the students. They enjoyed learning English. The first task was about answering questions in multiple choices form, hope the students get a high motivation to read and comprehend the text. And the second task was about students’ comprehension after they have read. They answered using their own words based on their own understanding. Most students answered those tasks very well and they had like the implementation of direct reading activity in the classroom. The students also stated that the technique was very helping in learning English and participating in the teaching learning process. They direct reading activity helped and motivated them in reading descriptive texts. The result of the observation also showed that students enjoyed learning English using direct reading activity. The technique which was used by the teacher can encourage them and motivate the students in reading activity, especially English lesson. From the observations which were done in the classroom, it could be seen that the students were interested in reading English by making some brainstorming to build an understanding about the text, then the students get easily to comprehend the texts’ means and motivate them to be a critical reader. For this reason, they agreed that the implementation of direct reading activity should be continued in the teaching and learning process. Based on the explanation above, the results of this study indicated that the researcher did the research in a hard way. Most of the students get difficulty in reading and the teacher wants to implement direct reading activity in reading skill to make students’ reading skills better. The description of the observation’s result above concluded that by implementing direct reading activity can make the students’ reading comprehension higher. The students are become active and they have high motivation to learn more about reading activity. It could be seen from the result of students’ works. The teacher was not give the answer directly because she knew exactly that her job here is guide the students. Harmer (2007: 110) states that when we are acting as a resource, we will want to be helpful and available, but at the same times we have to resist the urge of spoon feed our students so they will become over reliant on us. As a resource does not mean that the teacher should give all the answer without any recommendation, teacher should guide them then they can find the answer by themselves. The students enjoyed to give positive response toward the implementation of direct reading activity because direct reading activity is a natural part of what parents usually do in reinforcing increasingly better. And from the result above, the student get a good score in comprehension section and reading text, and the researcher knew that more than 70% students reached good scores. It means that the direct reading activity is a capable technique to build students’ motivation to read. And the last, the discussion below is focused on answering the two research questions mentioned previously. CONCLUSION AND SUGGESTION Conclusion The researcher got conclusion from the implementation of direct reading activity in teaching reading descriptive text which conducted in three meetings as the process to get the result of study. From the first and second meeting, the teacher stimulates and motivates the students in order to be ready and well prepared with the topic which is descriptive text. Then ask them to pay attention on what are teacher says. The teacher also shows the examples of descriptive text in front of the class and giving a model of good reading to students. After that teacher ask students to read the text correctly based on reading aspects (comprehension, vocabulary, content). Next, all of students answer the questions related to text, and some of them has answered the question from the teacher orally to measure their comprehension. She also controls the class and helps the students whether they have any difficulty to read or comprehend the text. After that she praised the students and gives comment about their work. After analyzing the students’ score as a response in the last meeting, the researcher draws some conclusions based on the data analysis and discussion in previous chapter: First, Teaching reading through direct reading activity was a good strategy. The classroom’s atmosphere became enjoyable to learn, especially in reading activity. Second, There was new a paradigm for the students that reading was not difficult to learn. Third, Direct reading activity was an interesting strategy that could be implemented in the teaching learning process. Suggestions The result of this study was that the teachers were successfully in terms of implementing direct reading activity as teaching strategies. In this case, the researcher suggests to teachers that she would be better to find or create more new strategy in teaching learning that can facilitate students to study. For example, the teacher can use direct reading activity that can invite students become active in teaching and learning activity, especially in reading because they have big responsibilities to create a successful language learning environment. REFERENCES Betts, E.A. 1946. Foundation of Reading Instruction. New York: American Book Company Brown, H Doughlas. 2004. Language Assesment Principal and Classroom Practices. San Fransisco State University: Longman Publisher Burns, C Paul, and Betty D. Roe., and Elinor P. Ross, 1984. Teaching Reading in TodaysElementary Schools. Boston: Houghton Mifflin Company Departemen Pendidikan Nasional. 2004. Standar Kompetensi Mata Pelajaran Bahasa Inggris SMP dan MTs. Jakarta: Depdiknas Eaness, Robin. 1997. Content Area Literacy: Teaching for Today and Tomorrow. Texas: Delmar Publisher Grabe, William, and Fredrika, L Stoller. 2002. Teaching and Researching Reading. Great Britain: Pearson Education Grabe, William, and Fredrika, L Stoller. 2002. Teaching and Researching Reading. Harlow England: Pearson Education Limited Harmer, Jeremy. 2007. The Practice of English Language Teaching Fourth Edition. England: Pearson Education Limited Many, J. &Flyfe I. 1996. The Effects of Using Directed Reading Thinking and Writing Activity on Scottish Elementary Students. Journal of Adolescent and Adult Literary, 55 (2), 104-119 Mc. Kenna and Robinson, R. 2002. Teaching Through Text: Reading and Writing In The Content Area (Third Edition). Boston: Allyn and Bacon Nunan, David. 1999. Second Language Teaching and Learning. Boston: Heinle and Heinle Publisher Nunan, David. 2003. Practical English Language Teaching. New York: McGraw-Hill Companies Rahim, Farida. 2005. Pengajaran Bahasa di Sekolah Dasar. Jakarta: Bumi Aksara Riley, D. 2006. The Effect of Directed Reading Thinking Activity on Low Reading Achievement First Grade Students. Dissertation International Abstract. 32 (4), 259-262 Spears, Deanne. 2006. Developing Critical Reading Skill (seventh edition). New York: McGraw-Hill Companies Simpson, A Elizabeth. 1957. Helping High School Students Read Better. Chicago: Science Research Associates CNC. Whitaker, C., Gambrell, L., and Morrow, L. 2004. Language and Literacy Learning in Schools. New York: Guilford Press, 130